The merits of exergy-based fault detection in petrochemical processes. (February 2019) - Marais, Henri; van Schoor, George; Uren, Kenneth R.
Highlights: Novel data abstraction that correlates with physical process structural information. Hybridisation of model-based and model-free fault detection and isolation scheme. Exergy-based characterisation could be used for fault detection and isolation. Real-time exergy calculation of an Autothermal Reformer in Aspen Hysys is proposed. Autothermal reformer is representative of process complexities. Exergy-based fault isolation proves to be viable in petrochemical processes. Abstract: The complexity and multi-domain nature of petrochemical (PC) plants make the application of conventional model-based fault detection and isolation (FDI) techniques a challenging endeavour. Although hybrid FDI schemes aim to address this shortfall, many are simply a combination of data-driven techniques that exclude physical system information. In this work, a hybrid approach to FDI of a PC process is proposed that is based on an exergy-data abstraction. Data from an actual system is abstracted to system exergy, based on physical knowledge of the system and then used as a diagnostic metric for the FDI scheme. In this paper, it is shown why energy-based approaches are lacking when considering petrochemical processes. After presenting a novel method for the real-time, automatic calculation of chemical exergy in Aspen HySys ® the applicability of exergy-based fault detection is investigated. Application of the exergy-based fault detection scheme shows a marked improvement over the energy-based approach with perfect detectability and isolability of the considered process faults. The exergy-based fault detection technique shows merit in comparison to the energy-based detection scheme. Additionally, and more importantly, exergy-based characterisation allows the use of more sophisticated model-based fault detection schemes to petrochemical processes.